Pengaruh Ketidakpuasan dan Sikap Mengeluh terhadap Perilaku Mengeluh Pengguan Mobil Suzuki di Kota Denpasar - Putra, I Gede Eka Sumanjaya; Wardana, I Made (E-Jurnal Manajemen, 2014)
The purpose of this study was to determine the influence of dissatisfaction and complaining attitude toward complaining user behavior Suzuki car in Denpasar. This study used a qualitative research using surveys and questionnaires to 105 respondents. It was found that dissatisfaction is a positive and significant effect on the behavior of users complaining Suzuki car in Denpasar and complaining attitude positive and significant effect on the behavior of users complaining Suzuki car in Denpasar. Attitude complained become dominant variables that affect the behavior of users complaining Suzuki car in Denpasar .   Keywords : Dissatisfaction, Complaining Attitude, Complaining Behavior
Keywords: Keywords : Dissatisfaction, Complaining Attitude, Complaining Behavior